(untitled) (REMUNOM, 2024)
This work aims to describe the data sink implementation for an IoT irrigation system named Hortência, previously developed. The paper assembles a real scenario for data collecting and formatting. Moreover, it performs a requirement analysis for database implementation for this IoT application.